1998
DOI: 10.1897/1551-5028(1998)017<2019:aadoss>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Depuration of Sediment-Sorbed C12- And C16-Polychlorinated Alkanes by Oligochaetes (Lumbriculus Variegatus)

Abstract: Abstract-Oligochaetes (Lumbriculus variegatus) were exposed to sediment spiked with four 14 C-polychlorinated alkanes (PCAs) (C 12 H 20 were readily available to sediment-ingesting oligochaetes, whereas C 16 H 21 Cl 13 had lower bioavailability. Uptake rates of the C 12 -PCAs were greater than the C 16 -PCAs, but half-lives (t 1/2 s) were greater for the C 16 -PCAs (t 1/2 ϭ 30-33 d) than for the C 12 -PCAs (t 1/2 ϭ 12-14 d). Biota-sediment accumulation factors were Ͼ1 for C 12 H 20 Cl 6 , C 12 H 16 Cl 10 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 20 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…This may be due to the differences in susceptibility to microbial and abiotic degradation between the different SCCP congeners. 21,34 However, differences in the transportation abilities of SCCP congeners with different chlorine contents may also influence the SCCP congener group profiles in environmental samples, which should be investigated in detail in future studies. 21,22,35 This work demonstrated that industrial wastewater discharges into the Liaohe River have resulted in SCCP contamination of the environment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This may be due to the differences in susceptibility to microbial and abiotic degradation between the different SCCP congeners. 21,34 However, differences in the transportation abilities of SCCP congeners with different chlorine contents may also influence the SCCP congener group profiles in environmental samples, which should be investigated in detail in future studies. 21,22,35 This work demonstrated that industrial wastewater discharges into the Liaohe River have resulted in SCCP contamination of the environment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, the degradation of SCCPs propelled by microbes in sediments may also play an important role (Persistent Organic Pollutants Review Committee, 2012;UK Environment Agency, 2007). It has been found that SCCPs become less susceptible to aerobic biodegradation as the carbon chain length increases (Fisk et al, 1998;Omori et al, 1987). That is to say, congeners with short carbon chains are more easily degraded in surface sediments, especially under the condition of many microorganisms, causing the further decrease of C 10 -CPs.…”
Section: Congener Group Profiles Sources and Environmental Behaviorsmentioning
confidence: 99%
“…The annual production has been continuously and rapidly increasing, up to 6 Â 10 5 tons in 2007 (De Boer et al, 2010) and 1 Â 10 6 tons in 2009 , so that CPs are released into the environment on a large scale (Ma et al, 2014a;Wang et al, 2012Wang et al, , 2014Zeng et al, 2011a;Zeng et al, 2012b). Because of their high Koc values (Fisk et al, 1998), CPs are easily adsorbed into sediments. They can be accumulated by the sediment-dwelling organisms and then pose potential risks to humans after being further accumulated through the food chain (Houde et al, 2008;Ma et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…As for sediment and soil samples, the most abundant congeners possessed 5-10 chlorine atoms (Chen et al, 2011;Gao et al, 2012;Hüttig and Oehme, 2006;Iino et al, 2005;Iozza et al, 2008;Marvin et al, 2003;Štejnarová et al, 2005;Tomy et al, 1999;Wang et al, 2013bWang et al, , 2013cZeng et al, 2011aZeng et al, , 2012cZeng et al, , 2013, quite similar to those in food, human milk and wildlife samples (Harada et al, 2011;Thomas et al, 2006;Zeng et al, 2011b). Regardless of the method limitation in analyzing C 10 -congeners with 1-4 chlorine atoms (Moore et al, 2004;Reth et al, 2005), the low stability of C 10 -congeners with 1-4 and 12-13 chlorine atoms was verified by the experimental data, indicating the instability and higher biodegradability of C-10 -congeners with low or high chlorination degree in the aerobic or aerobic environment, respectively (Allpress and Gowland, 1999;Chen et al, 2011;Fisk et al, 1998;Omori et al, 1987).…”
Section: Effect Of Chlorination Degree On Thermodynamic Properties Ofmentioning
confidence: 99%